'Rhodesians' in South Africa : a study of immigrants from Zimbabwe - Simon, Alan (Rhodes University, Faculty of Humanities, Department of Sociology, 1984)
Although most whites have remained in Zimbabwe after independence and not all who have emigrated came to South Africa, large numbers established themselves as an immigrant community in this country. The aim of this study is to "sociologically capture" this community's views about their past experiences in Rhodesia/Zimbabwe and their present experiences in South Africa. This is done by employing a generative methodological procedure whereby members of the target population themselves generated issues considered to be of importance to their previous and new situational contexts. As it was not possible to obtain a random sample of all Zimbabwean immigrants in South Africa, questionnaire data were collected from four separate categories of respondents. In addition, depth interviews were conducted and thus responses have been analysed both qualitatively and quantitatively. The findings demonstrate that for the most part, few "Zimbabweans" - whites who are reasonably accepting of the new socio-political order in independent Zimbabwe - have come to South Africa. Rather, most of the immigrants, whose views were canvassed in this research investigation, seem to be bitter "Rhodesians" who have been unable to accept change and integration and the consequent loss of white privilege in the new Zimbabwe. These recent immigrants have not found all things to their satisfaction in South Africa moreover, despite the similar socio-political structures in former Rhodesia and contemporary South Africa.
Keywords: Zimbabweans -- South Africa -- Foreign population; Zimbabwe -- Emigration and immigration; South Africa -- Emigration and immigration